Avaliação da proporção de células mononucleares e de MMP-2 e 9 na periodontite crônica em fumantes e não-fumantes - Cruz, Luis Eduardo Rilling da Nova (2010)
The objective of the present study was the immunohistochemical evaluation of the proportion of mononuclear cells and the expression of MMP-2 and 9 on chronic periodontitis between smokers and non-smokers. From the 127 patients examined 31(16 non-smokers and 15 smokers) fulfill the inclusion criteria were included in the study. These patients underwent surgical procedures and 31 biopsies were collected and divided in two parts, one for histological preparation and the other for zymography. Each sample was histologically processed and exposed to monoclonal antibodies for B cells (anti-CD20), memory T cells (anti-CD45RO) and macrophages or monocytes (anti-CD68) detection. The samples showed a similar pattern, with connective tissue rich in inflammatory cells. The histometric analysis showed that the total amount of mononuclear inflammatory cells labeled did not differ significantly between smokers and non-smokers (p> 0.05). Evaluating each cell type separately, significant differences were not detected between groups (p> 0.05). When stratifying the samples into regions (coronal, middle and apical third) to evaluate the presence of individual cell types in each region significant differences between the groups were not detected (p> 0.05). The zymography of the samples suggested that the expression of MMP-2 and 9 showed no statistically significant differences between the two groups (p> 0.05). Thus, within the limits of this study, we can conclude that sites with chronic periodontitis in smokers and non-smokers did not differ in the amount of mononuclear inflammatory cells and in the expression of MMPs 2 and 9.